2019
DOI: 10.1007/s10295-019-02241-y
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial mutations for carotenoid production identified from laboratory-evolvedSaccharomyces cerevisiae

Abstract: Adaptive laboratory evolution (ALE) is a powerful tool used to increase strain fitness in the presence of environmental stressors. If production and strain fitness can be coupled, ALE can be used to increase product formation. In earlier work, carotenoids hyperproducing mutants were obtained using an ALE strategy. Here, de novo mutations were identified in hyperproducers, and reconstructed mutants were explored to determine the exact impact of each mutation on production and tolerance. A single mutation in YMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…17 Moreover, Godara et al revealed that the increase in β-carotene production level was correlated with tolerance to oxidative stress. 25 Strong directional selection might enhance evolvability by favoring the accumulation of beneficial mutations facilitating both fitness and evolvability. 26 Given these studies, an integrated strategy of mutagenesis by ARTP and evolution in periodic H 2 O 2 treatment was conducted according to the protocols above (Figure 3A).…”
Section: ■ Results and Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Moreover, Godara et al revealed that the increase in β-carotene production level was correlated with tolerance to oxidative stress. 25 Strong directional selection might enhance evolvability by favoring the accumulation of beneficial mutations facilitating both fitness and evolvability. 26 Given these studies, an integrated strategy of mutagenesis by ARTP and evolution in periodic H 2 O 2 treatment was conducted according to the protocols above (Figure 3A).…”
Section: ■ Results and Disscussionmentioning
confidence: 99%
“…Meanwhile, previous research reported that carotenoids were effective in protecting cells from ROS due to their antioxidant properties. 25 We then examined the ROS levels of yZK002 and yZK006 at different stages using the fluorometer. Strain yZK006 showed a lower ROS level and higher lycopene production compared with strain yZK002 (Figures 3C and 5A).…”
Section: ■ Results and Disscussionmentioning
confidence: 99%
“…New achievements reached in genetic and metabolic engineering of microorganisms made it possible to optimize host microorganisms to use as advanced microbial cell factories. It was demonstrated that the best combinations of mutations identified for β-carotene production were also beneficial for the production of lycopene [140]. It was shown that recombinant microbial cell factories can be engineered on the basis of an oleaginous yeast, Yarrowia lipolytica, to produce astaxanthin by submerged fermentation [126].…”
Section: Biotechnologymentioning
confidence: 99%
“…Recently, a study directed to metabolic engineering of S. cerevisiae demonstrated the potential of a yeast-based process for β-carotene production [141]. Recent reviews give insights into microbial engineering principles for the overproduction of carotenoids and describe key strategies and current advances in engineering of the metabolism of carotenoid-producing microorganisms for maximizing carotenoid production [140,142,143]. It was reported that chemical mutagenesis led to the obtaining of Bl.…”
Section: Biotechnologymentioning
confidence: 99%
“…Carotenoids are an important class of lipophilic natural products with antioxidant properties and are widely used as nutraceuticals in the food and health industries. Saccharomyces cerevisiae is an attractive microbial host for producing carotenoids (Ma et al, 2018; Xie et al, 2015), and multiple engineering strategies have been tested in this yeast to improve carotenoid production, including disrupting bypass‐pathway genes, increasing metabolic flux toward the mevalonate (MVA) pathway and increasing the size of lipid droplets (LDs; Chen et al, 2016; Godara et al, 2019; Ma et al, 2018; Miao et al, 2011; Shiba et al, 2007; Trikka et al, 2015). However, carotenoids production is still far from its theoretical yield, and there is still a need for further improvement.…”
Section: Introductionmentioning
confidence: 99%